Pengaruh Perceived Value terhadap Intention to Comply Pengunjung Museum Negeri Provinsi Sulawesi Utara - Christine Patricia Elvano Porajow; Made Antara; I Wayan Suardana (Magister Tourism Study, Faculty of Tourism, Udayana University, 2021)
The phenomenon of an increase in foreign tourist visitors in the North Sulawesi Province State Museum is an urgency factor to do this research as a form of evaluation of consumption patterns related to sustainable behavior when visiting, especially in crowded situations with low levels of supervision. The purpose of this study was to determine the extent to which visitor value consumption takes a role in museum sustainability through intention to comply. Primary research data obtained from questioners, observations, and interviews with the accidental sampling method on 100 respondents of foreign tourists. This research uses a quantitative approach SEM - Smartpls 3.0 which is assessed through a Likert scale. The results of statistical data analysis show that motivation, consumer perceived value, and satisfaction significantly influence the intention to comply with foreign tourists on the rules in the museum and consumer perceived value is the dominant variable affecting satisfaction, therefore the museum is obliged to manage and facilitate consumption value through visitor perceptions museum. Keywords: Museum visitor motivation, Consumer perceived value visitors, Museum visitor satisfaction, Intention to comply museum visitors